Journeying into the world of identities: a study on the select fiction of Shyam Selvadurai - Thushara Mohan (Post Graduate and Research Department of English, Sree Kerala Varma College, 2023)
Shyam Selvadurai is a prominent writer now living in Toronto, Canada. His literary pursuits had made him a significant figure in both Canada and Sri Lanka. The thesis analyses the gay, ethnic and intersectional identities in Shyam Selvadurai’s select fiction including Funny Boy (1994), Cinnamon Gardens (1998), Hungry Ghosts (2013) and Swimming in the Monsoon Sea (2005). The thesis had endeavored to furnish multiple perspectives on the aspects of gender and ethnicity in the select texts. The study had simultaneously used both textual and theoretical analysis while exploring the different dimensions of gender and identity. All the novels chosen for the study except Swimming in the Monsoon Sea depicts different periods of Sri Lankan ethnic riots. In all these novels Selvadurai introduces gay protagonists whose sexual identities intersect with their ethnic and racial identities thus adding to their marginalization. In the due course of the textual exploration, the study had attempted to facilitate a comparative analysis of the representation of the protagonists. The thesis had focused on the portrayal of diverse identities in the novels, at the backdrop of the ethnic conflicts of Sri Lanka. It had discussed the intersection of racial and gender identities and the subsequent marginalization encountered by the protagonists on the basis of gender identity, ethnicity, caste and class. The analysis in fact had endeavored to provide an analytical and comprehensive overview of the select texts through a detailed and holistic approach.
1. Introduction -- 2. Gay identity and the select narratives -- 3. ethnic identity and conflicts: aspects and dimensions -- 4. Intersectional Identities -- 5. Conclusion -- 6. Recommendations
Thesis (Ph.D)- Sree Kerala Varma College, Post Graduate and Research Department of English, 2023.
Keywords: Ethnicity; Gay identity; Identity; Intersectionality; Marginalization; Race